DECISION SUPPORT SYSTEM FOR SELECTING BANJAR RESTAURANT IN BANJARMASIN CITY USING SIMPLE ADDITIVE WEIGHTING METHOD - Dalle, Juhriyansyah; Windarsyah, Windarsyah; Ridho, Rasyid (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2018)
This study aims to build a decision support system (DSS) application for selecting Banjar restaurant using website-based Simple Additive Weighting (SAW) method. This application can be accessed by all users, both via smartphone and laptop/computer. Users can access the application to assist the selection of Banjar restaurant based on the weighting of the required criteria. Data of Banjar restaurants was obtained from the Tourism Office of South Borneo Province. Decision support system for selecting Banjar restaurant was built using XAMPP as a server, MySQL as a database, HTML (Hypertext Markup Language), JavaScript framework using jQuery, PHP framework (Hypertext Preprocessor) using Laravel, and CSS framework (Cascading Style Sheet) using Bootstrap. Meanwhile, the system development used was waterfall method. The parameters used to choose a Banjar restaurant were in terms of facilities, opening time, price, variety of menus, and capacity. The result of this research is a decision support system application that can provide results in the form of Banjar restaurant alternatives based on rankings from the highest to lowest values generated from calculations using SAW method. This system is also equipped with distance that appears automatically between the user's location and the restaurant, and time that adjusts and shows which restaurants are open at the accessing time. From the analysis results of the Calculation Score Interpretation (CSI) average, the results of users? responses in general from the Tourism Office, tourists, or prospective consumers, stated that the system is very suitable to be used as a reference in selecting Banjar restaurant in Banjarmasin City, with an 88.8% CSI.